PENGARUH REKRUTMEN PENEMPATAN DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT. TUNGGAL YUNUS ESTATE PETAPAHAN - Rahma A Mayang; Machasin Machasin; Rifqi Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of recruitment, placement and training on employee performance at PT. Tunggal Yunus Estate Petapahan with the aim to determine the effect of recruitment on the performance of employees of PT. Tunggl Yunus Estate Petapahan, to determine the effect of placement on employee performance at PT. Tunggl Yunus Estate Petapahan, to determine the effect of training on employee performance at PT. Tunggl Yunus Estate. to determine the effect of recruitment, placement and training on the performance of employees at PT. Tunggl Yunus Estate Petapahan. The population in this study includes all employees at PT. Tunggal Yunus Estate Petapahan, totaling 88 people. Sampling that has been selected is the census method (88 employees at PT. Tunggal Yunus Estate Petapahan). The technique of collecting data by using a questionnaire. Multiple linear regression analysis method using SPSS. The results of the tests that have been done, regression test partially that each independent variable studied (recruitment, placement and training) has an influence on the dependent variable (performance), this is indicated by the results that the recruitment variable has a significant effect on employee performance, the placement variable has an effect significant on employee performance, while the training variable has a significant effect on employee performance at PT. Tun ggal Yunus Estate Petapahan. Meanwhile, the simultaneous regression test shows that the independent variables studied (recruitment, placement and training) have an influence on the dependent variable (employee performance). The amount of influence caused by the three independent variables is 60.8%, while the remaining 39.2% is influenced by other variables not examined in this study.Keywords: Recruitment, Placement, Training, Performance